2019
DOI: 10.12944/crnfsj.7.3.26
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Effects of Food Colorants Erythrosine and Tartrazine on Zebrafish Embryo Development

Abstract: Erythrosine and tartrazine are common artificial food additives which have become a part of daily human consumption. Advised daily intake values for these agents are set strictly, however, the actual intake is much higher than the recommended ADI. A higher intake of erythrosine and tartrazine is shown to exhibit adverse effects in mammalian models, and is thus a matter of public health concern. In this study we have assessed and compared the dose-dependent effects of erythrosine and tartrazine on inducing oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 33 publications
(39 reference statements)
0
10
0
Order By: Relevance
“…Another explanation for difficulty hatching is neuromuscular deficiencies that cause weakening of spontaneous muscle movements (De la Paz et al 2017). As a matter of fact, a decrease in hatching rate was observed in zebrafish embryos exposed to different toxicants including azo dyes (Gupta et al 2019;Joshi and Katti 2018;Li et al 2017;Suvarchala and Philip 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Another explanation for difficulty hatching is neuromuscular deficiencies that cause weakening of spontaneous muscle movements (De la Paz et al 2017). As a matter of fact, a decrease in hatching rate was observed in zebrafish embryos exposed to different toxicants including azo dyes (Gupta et al 2019;Joshi and Katti 2018;Li et al 2017;Suvarchala and Philip 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Jiang et al (2020) found the CL (I) 50, 96 h value of 47.10 mM (25.1 g.L -1 ). Of these papers, those of Gupta et al (2019) and Silva and Fracácio (2020) described deformities that were found in the embryonic and larval development of D. rerio, suggesting that the tartrazine dye, once released into the aquatic environment, compromises aquatic life (Table 2).…”
Section: Ecotoxicological Analysesmentioning
confidence: 99%
“…Therefore, for this value to be considered safe, other stages of the species' development must be tested. The literature also reports that the chorion can be impervious to a good number of pollutants; however, studies have proven that the tartrazine yellow dye has overcome this protective barrier (JOSHI; KATTI, 2017;GUPTA et al, 2019;FRACÁCIO, 2020), and the dye also accelerated the embryo hatch rates (from 72 hpf to 48 hpf).…”
Section: Basu Andmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, skeletal and morphological malformations were also noticed in the chick embryos-treated with SY and Tz [6] . Also, Gupta et al [7] found that erythrosine and Tz were teratogenic to zebrafish embryos. Moreover, some of food additives were proved to induce DNA damage in bacteria, fungi, insects, and mammalian cells in vivo and in vitro.…”
Section: Introductionmentioning
confidence: 99%